Key Influencers of College Students’ Learning Outcomes in Online Education in Chengdu - Wang, Miaoru (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study aims to identify and explore the factors influencing college students’ satisfaction and learning outcomes in online education in Chengdu, China. Research design, data and methodology: A quantitative research method was employed, with data collected through questionnaires distributed to the target population. To ensure the validity and reliability of the instrument, project-to-objective consistency (IOC) and Cronbach’s Alpha tests were conducted before survey distribution. The collected data were analyzed using confirmatory factor analysis (CFA) and structural equation modeling (SEM) to test the research hypotheses, assess the model’s goodness of fit, and explore causal relationships between variables. Results: The analysis results indicate that the proposed conceptual model effectively predicts and explains learning outcomes (LO) in online education. Student satisfaction (SS) emerged as a key predictor of learning outcomes, directly influencing student engagement and performance. Additionally, factors such as teachers’ technology readiness, structured teaching approaches, students’ technology readiness, and self-efficacy were found to have a direct impact on student satisfaction. Conclusions: Based on these findings, the study recommends that higher education institutions enhance both students’ and faculty members’ technological readiness and foster students’ self-efficacy to improve satisfaction and learning outcomes in online education.